Thermodynamic based economic and environmental analyses of an industrial cogeneration system. (25th July 2019) - Caglayan, Hasan; Caliskan, Hakan
Highlights: Thermodynamic based environmental and enviroeconomic assessments of a natural gas fired cogeneration system. Consideration of CO2 environmental pollution for environmental assessments. Effect of various environment temperatures on the analyses of industrial process. Abstract: This paper presents first and second laws of thermodynamics based environmental and enviroeconomic analyses as well as thermoeconomic and environmental assesments of the natural gas fired cogeneration system of the ceramic manufacturing plant including wall and ground tile dryers and a gas turbine system in a factory building. The environment temperatures are assumed as 10 °C, 15 °C, 20 °C, 25 °C and 30 °C. The thermoeconomic values are found to be 2766.132 kW h/$ for the ground tile dryer, 2479.726 kW h/$ for the wall tile dryer, 1595.575 kW h/$ for the combustion chamber, 543.212 kW h/$ for the cogeneration (overall) system, 239.074 kW h/$ for the gas turbine, while the air compressor is zero. The maximum total exergoeconomic parameter is calculated to be 11331.659 kW h/$ for the combustion chamber at 30 °C environment temperature. The increasing in the environment (dead state) temperature leads to increase in the total exergoeconomic parameter for the combustion chamber, air compressor and cogeneration system; while these parameters decrease for both of the dryers. For gas turbine, there is no correlation between temperature (dead state) and total exergoeconomic parameter. Furthermore, environment and enviroeconomic parameters are determined as 27580.74 kg-CO2 /day and 399.92 $/day for the wall tile dryer, and 41900.32 kg-CO2 /day and 607.55 $/day for the ground tile dryer, respectively.